Artículo Científico - Analysis of Transmissión Measurement of ISDB - T - Haro Báez, Raúl Vinicio (2012)
This paper shows the performance of standard ISDB-T, based on the signal generated by a laboratory transmitter and the signal generated by the transmitter of the channel Ecuadorian state (ECTV, which power, the modes of operation an the modulation accuracy were analyzed.